EFFECT OF KAPIKACCHU CHURNA AND STHIRADIPANCHAMOOLA YAPANA BASTI KARMA IN THE MANAGEMENT OF KSHEENASHUKRATA W.S.R. TO OLIGOSPERMIA: A CASE STUDY - Sasane, *Prashant; Kishor Joshi, Ram (AYUSHDHARA, 2016)
Ayurveda is a science of life and it has taken the foremost place in the management of life style disorder. Oligospermia refers to semen with low concentration of sperm and is a common finding in male infertility. Often semen with a decreased sperm concentration may also show significant abnormalities in sperm morphology and motility. In general Male infertility factors are suspected of contributing to infertility in almost 40% of infertile couples,A male patient aged 25 years was presented with desire to get child and other associated symptoms were Daurbalya (weakness),Timira Darshana(black out), Mukha Shosa (dryness of mouth), Panduta (paleness), Shrama (Fatigue or Tiredness), Aharsana (weak penile erection), Maithune Ashakti (Problematic or not satisfactory coitus), Rati Anabhimukhata (Lack of sexual desire), & Medhra-Vrishana Vedana (Pain in scrotum and penis). On basis of symptoms and semen analysis he was diagnosed as case of Ksheenashukra (oligospermia). The patient was managed with Kapikacchu churna and Sthiradipanchamoola Yapana Basti Kala Basti karma. Result were assessed by grading for sexual parameters like sexual desire, erection, ejaculation and symptoms of Kshinashukra. Seminal Parameters was done by Semen Analysis. Kapikacchu churna and Basti treatment gave significant improvement in all the symptoms of Kshinashukra and seminal parameters like sperm count, motility.